Ammonia recovery from chicken manure digestate using polydimethylsiloxane membrane contactor - ÇALLI, BARIŞ (ELSEVIER SCI LTD, 2018)
The ammonia removal and recovery performance of a non-porous tubular PDMS membrane was evaluated in this study by immersing it into chicken manure (CM) digestate and operating it in sweep gas mode at different air flowrates, pH values and total ammonium nitrogen (TAN) concentrations. The TAN removal flux achieved as 1.33 +/- 0.10 g/m(2)/day was comparable to the values obtained with porous membranes used in ammonia recovery from anaerobic digestate. The relative proportion of ammonium and free ammonia, which depends on pH, temperature and TAN concentration of digestate, was found to be more effective than the sweep gas flow rate on ammonia recovery. In this study, it was shown for the first time that the low cost non-porous tubular PDMS membrane contactor is a promising technology for recovery of ammonia from nitrogen rich wastes such as CM digestate. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Ammonia removal flux; Free ammonia; Gas diffusion; Non-porous; Sweep gas; GAS-PERMEABLE MEMBRANES; ANAEROBIC-DIGESTION; WASTE-WATER; DAIRY MANURE; CO-DIGESTION; REMOVAL; DISTILLATION; ABSORPTION; BIOGAS; PH